Renal Leiomyoma and Leiomyosarcoma: A Study of 57 Cases. (November 2016) - Gupta, Sounak; Jimenez, Rafael E.; Folpe, Andrew L.; Cheville, John C.
Abstract : Primary renal leiomyomas and leiomyosarcomas are rare, and there is a paucity of data regarding the pathologic features and outcomes of patients with these tumors. The objective of this study was to review a large series of renal smooth muscle tumors, in order to more fully elucidate their natural histories. Fifty-seven renal smooth muscle tumors were reviewed for various histopathologic features, and leiomyosarcomas were graded using the French Federation of Cancer Centers (FNCLCC) system. Tumor cores in tissue microarrays were evaluated for smooth muscle actin, desmin, h-caldesmon, calponin, myogenin, cytokeratin (OSCAR), CD117, Ki67, estrogen receptor (ER), progesterone receptor (PR), and Wilms tumor 1 (WT1). Leiomyomas were selected on the basis of preexisting diagnostic criteria, which included a lack of cytologic atypia, necrosis, and mitotic activity (0 to 1 mitoses/10 hpf). These were found to have a strong predilection for women, tended to arise from the renal capsule, were small (mean size, 4.2 cm), and had a low Ki67 proliferative rate (mean 1.4%). In addition, they uniformly expressed all smooth muscle markers and were ER/PR/WT1 positive in nearly all cases. In 10 patients with clinical follow-up, none had a tumor recurrence. In contrast, leiomyosarcomas had an equal sex distribution, were larger (mean size, 9.8 cm), had significantly higher mitotic activity (mean 8.6 mitoses/10 hpf), with most being FNCLCC grade 2. Leiomyosarcomas expressed at least 1 muscle marker, higher Ki67 proliferative activity (mean 20.4%) than leiomyomas, and most were ER/PR/WT1 negative. Tumor recurrence occurred in 65% of patients, and 35% of patients died of disease. This study therefore validates existing criteria to distinguish between leiomyomas and leiomyosarcomas. Abstract : Supplemental Digital Content is available in the text.